PROGRAM GBL (GAK BANJIR LAGI) UPAYA RECOVERY PENANGGULANGAN BENCANA PASCA BANJIR BANDANG DESA SUKAWENING KABUPATEN GARUT - Dika Abdul Latif; Ishmah Hamidah; Iin Patimah; Andhika Lungguh Perceka; Hairani Rahatyu (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
The flash flood disaster that occurred in Sukawening District, Garut Regency on November 27, 2022, resulted in several impacts for the community. Apart from material losses, this flash flood also left deeptrauma for the community. The Non- Flood Again Program (GBL) is here to assist in handling theaftermath of the flash flood in Sukawening Village. The program is a program designed by STIKesKarsa Husada Garut students in the Village Community Health Development (VCHD) activity. Theprogram implemented focuses on three aspects of activity, namely: (1) disaster mitigation seminars, (2)tree planting, (3) trauma healing. The results of the activity showed that there was an increase in the understanding of the surrounding community regarding disasters, besides thatthe community began tounderstandand care about the importance of protecting the surrounding environment.